Synchronous radial 1H and 23Na dual‐nuclear MRI on a clinical MRI system, equipped with a broadband transmit channel. Issue 4 (3rd February 2017) - Kaggie, Joshua D.; Sapkota, Nabraj; Thapa, Bijaya; Jeong, Kyle; Shi, Xianfeng; Morrell, Glen; Bangerter, Neal K.; Jeong, Eun‐Kee
Abstract: The purpose of this work was to synchronously acquire proton ( 1 H) and sodium ( 23 Na) image data on a 3T clinical MRI system within the same sequence, without internal modification of the clinical hardware, and to demonstrate synchronous acquisition with 1 H/ 23 Na‐GRE imaging with Cartesian and radial k‐space sampling. Synchronous dual‐nuclear imaging was implemented by: mixing down the 1 H signal so that both the 23 Na and 1 H signal were acquired at 23 Na frequency by the conventional MRI system; interleaving 1 H/ 23 Na transmit pulses in both Cartesian and radial sequences; and using phase stabilization on the 1 H signal to remove mixing effects. The synchronous 1 H/ 23 Na setup obtained images in half the time necessary to sequentially acquire the same 1 H and 23 Na images with the given setup and parameters. Dual‐nuclear hardware and sequence modifications were used to acquire 23 Na images within the same sequence as 1 H images, without increases to the 1 H acquisition time. This work demonstrates a viable technique to acquire 23 Na image data without increasing 1 H acquisition time using minor additional custom hardware, without requiring modification of a commercial scanner with multinuclear capability.